Epidemiology of capybara-associated Brazilian spotted fever. - Hermes R Luz; Francisco B Costa; Hector R Benatti; Vanessa N Ramos; Maria Carolina de A Serpa; Thiago F Martins; Igor C L Acosta; Diego G Ramirez; Sebastián Muñoz-Leal; Alejandro Ramirez-Hernandez; Lina C Binder; Marcio Port Carvalho; et al. (Public Library of Science (PLoS), 2019)
BACKGROUND:Brazilian spotted fever (BSF), caused by the bacterium Rickettsia rickettsii, has been associated with the transmission by the tick Amblyomma sculptum, and one of its main hosts, the capybara (Hydrochoerus hydrochaeris). METHODS:During 2015-2019, we captured capybaras and ticks in seven highly anthropic areas of São Paulo state (three endemic and four nonendemic for BSF) and in two natural areas of the Pantanal biome, all with established populations of capybaras. RESULTS:The BSF-endemic areas were characterized by much higher tick burdens on both capybaras and in the environment, when compared to the BSF-nonendemic areas. Only two tick species (A. sculptum and Amblyomma dubitatum) were found in the anthropic areas; however, with a great predominance of A. sculptum (≈90% of all ticks) in the endemic areas, in contrast to a slight predominance of A. dubitatum (≈60%) in the nonendemic areas. Tick species richness was higher in the natural areas, where six species were found, albeit with a predominance of A. sculptum (≈95% of all ticks) and environmental tick burdens much lower than in the anthropic areas. The BSF-endemic areas were characterized by overgrowth populations of A. sculptum that were sustained chiefly by capybaras, and decreased populations of A. dubitatum. In contrast, the BSF-nonendemic areas with landscape similar to the endemic areas differed by having lower tick burdens and a slight predominance of A. dubitatum over A.sculptum, both sustained chiefly by capybaras. While multiple medium- to large-sized mammals have been incriminated as important hosts for A. sculptum in the natural areas, the capybara was the only important host for this tick in the anthropic areas. CONCLUSIONS:The uneven distribution of R. rickettsii infection among A. sculptum populations in highly anthropic areas of São Paulo state could be related to the tick population size and its proportion to sympatric A. dubitatum populations.